2015
DOI: 10.1002/cssc.201403332
|View full text |Cite
|
Sign up to set email alerts
|

Titania‐Supported Catalysts for Levulinic Acid Hydrogenation: Influence of Support and its Impact on γ‐Valerolactone Yield

Abstract: A series of titania-supported ruthenium and platinum catalysts was investigated in the levulinic acid hydrogenation towards γ-valerolactone, a key reaction for the catalytic transformation of biomass. It was shown that various morphologies and phases of titania strongly influence the physicochemical and catalytic properties of supported Ru and Pt catalysts in different ways. In the case of the catalyst supported on mixed TiO2 phases, Ru particles are exclusively located on the minority rutile crystallites, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 48 publications
9
83
1
1
Order By: Relevance
“…The observation on the basis of TEM that well-dispersed Ru on TiO 2 (A100) with small average Ru nanoparticle sizes are attainable for some of the catalysts is surprising considering a recent study on Ru/TiO 2 (A100) [32]. Here, the wet impregnation of ruthenium (Ru(acac) 3 on large surface-area TiO 2 (A100, 83-336 m 2 /g), followed by calcination at 200°C in air and a reduction at similar conditions with hydrogen resulted in an inhomogeneous metal distribution with very large Ru nanoparticles (as seen by TEM) and small ones in the micropores.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The observation on the basis of TEM that well-dispersed Ru on TiO 2 (A100) with small average Ru nanoparticle sizes are attainable for some of the catalysts is surprising considering a recent study on Ru/TiO 2 (A100) [32]. Here, the wet impregnation of ruthenium (Ru(acac) 3 on large surface-area TiO 2 (A100, 83-336 m 2 /g), followed by calcination at 200°C in air and a reduction at similar conditions with hydrogen resulted in an inhomogeneous metal distribution with very large Ru nanoparticles (as seen by TEM) and small ones in the micropores.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Furthermore, a comparison of the catalytic transfer hydrogenation of levulinate esters using Ru(OH) x /TiO 2 [31], with anatase, rutile and anatase-rutile titanias, showed the anataserutile-based catalyst to perform best (86% for TiO 2 (A); > 99% for TiO 2 (R) and TiO 2 (A75:R25)). Recently, Ruppert et al reported a detailed study on the influence of various TiO 2 supports (anatase, rutile and mixtures thereof) on the Ru-catalyzed LA hydrogenation [32]. A Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it is reported in literature that mixing acid catalysts with Ru metal catalysts promoted hydrogenation and bifunctional catalysts are active and recyclable in aqueous solution [18,34]. The nature of the support and the synthesis method influence the catalytic activity significantly in hydrogenation reactions [35]. Considering the relatively high cost and low availability of ruthenium, catalyst robustness is a key issue for any practical application [36].…”
Section: Introductionmentioning
confidence: 99%